UNCOVERING GENETIC PATTERNS OF THE BARRED MUDSKIPPER ALONG THE WEST COAST OF BENGKULU USING THE COI GENE - Fanni Khoirillah; Zuliyati Rohmah; Rury Eprilurahman; Tuty Arisuryanti (SEAMEO BIOTROP, 2026)
ARTICLE HIGLIGHTS- First genetic baseline for mudskipper in western Sumatra- One shared lineage links Bengkulu to southern Java- High connectivity along an open, shallow coastline- Coastal tides and currents shape genetic patterns- Findings support regional scale conservation planningABSTRACTThe barred mudskipper, Periophthalmus argentilineatus, is an amphibious gobiid fish that exhibits fully terrestrial behavior during low tides. Previous research has suggested the presence of cryptic species within this taxon, complicating species identification due to highly similar morphological traits. Despite its ecological importance in intertidal ecosystems, information on the genetic variation and population structure of P. argentilineatus in Sumatra remains limited, and no such data have been reported from the West Coast of Bengkulu. Therefore, this study aimed to assess the genetic diversity and population structure of P. argentilineatus along this coastline using the mitochondrial COI gene. A total of 30 individuals were collected from three locations, i.e., Air Hitam Coast, Baai Mangrove Forest, and Teluk Sepang Coast. The COI gene was amplified (approximately 660 bp), and a final aligned fragment of 630 bp was used for genetic analyses. Phylogenetic reconstruction placed all Bengkulu samples within a single lineage corresponding to Clade C previously reported from southern Java. Clades A and B were not detected in the study area. Genetic distances among individuals ranged from 0.00 – 0.80%, indicating close relatedness within this lineage. Sequence analysis identified nine variable sites, including two parsimony-informative positions, resulting in nine haplotypes. Haplotype diversity was moderate (Hd = 0.708), whereas nucleotide diversity was low (π = 0.00182). Negative Tajima’s D values suggest recent demographic expansion or ongoing connectivity among populations. AMOVA and Fst analyses indicated low or undetectable genetic differentiation among sampling sites, consistent with substantial gene flow along the coastline. These findings establish a baseline genetic reference for P. argentilineatus in Bengkulu and contribute to understanding regional population connectivity along the western Indonesian coastline.